CEPHALOSPORINS AS A POTENTIAL RISK FACTOR FOR UROLITHIASIS: A CASE-CONTROL STUDY - KRISHNAKUMAR JANARTHANAM; GANDHIMATHI R (Asian Journal of Pharmaceutical and Clinical Research, 2025)
The study aimed to explore the impact of Oxalobacter formigenes colonization and cephalosporin antibiotic treatment on urinary oxalate, calcium, and citrate levels, with a focus on evaluating the bacterium’s role in mitigating the risk of calcium oxalate kidney stone formation. An observational, case-control study was conducted involving 350 control subjects and 280 kidney stone patients. Participants were stratified based on recent cephalosporin use and O. Formigenes colonization. Results demonstrated that O. Formigenes colonized individuals consistently exhibited lower urinary oxalate and calcium levels and higher citrate levels compared to non-colonized counterparts. Cephalosporin treatment exacerbated urinary biochemical imbalances, further increasing oxalate and calcium excretion while reducing citrate levels, particularly in non-colonized individuals. This highlights the protective role of O. Formigenes in maintaining urinary biochemical homeostasis and reducing kidney stone risk. The findings underscore the need for strategies to preserve gut microbiota, especially O. Formigenes, during antibiotic therapy to mitigate metabolic consequences and prevent urolithiasis.